2011
DOI: 10.1016/j.ejphar.2011.01.036
|View full text |Cite
|
Sign up to set email alerts
|

Association between melanism, physiology and behaviour: A role for the melanocortin system

Abstract: The melanocortin system is implicated in the expression of many phenotypic traits. Activation of the melanocortin MC 1 receptor by melanocortin hormones induces the production of brown/black eumelanic pigments, while activation of the four other melanocortin receptors affects other physiological and behavioural functions including stress response, energy homeostasis, anti-inflammatory and sexual activity, aggressiveness and resistance to oxidative stress. We recently proposed the hypothesis that some melanocor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
140
1
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 126 publications
(151 citation statements)
references
References 42 publications
9
140
1
1
Order By: Relevance
“…In birds, genetic colour polymorphism-defined as a highly heritable variation in expressed plumage coloration that is independent of age and sex-is often associated with variation in life-history traits, including physiology, behaviour and immunity [3,4]. These associations may result from pleiotropic effects of genes regulating melanogenesis, such as the melanocortin-1-receptor (Mc1r).…”
Section: Introductionmentioning
confidence: 99%
“…In birds, genetic colour polymorphism-defined as a highly heritable variation in expressed plumage coloration that is independent of age and sex-is often associated with variation in life-history traits, including physiology, behaviour and immunity [3,4]. These associations may result from pleiotropic effects of genes regulating melanogenesis, such as the melanocortin-1-receptor (Mc1r).…”
Section: Introductionmentioning
confidence: 99%
“…On museum skin specimens, we counted and measured the size of black eumelanic feather spots, as well as measuring pheomelanin-based coloration, which varies from white to dark red. In European Barn Owls (T. a. alba, T. a. guttata), these three plumage traits are genetically correlated with behavioral and physiological processes (Roulin and Ducrest 2011). For instance, smaller-spotted and redder pheomelanic owls have a higher appetite , and larger-spotted owls are more resistant to parasitism and to various sources of stress that induce a rise in glucocorticoids (Roulin et al 2000, Almasi et al 2012.…”
Section: Introductionmentioning
confidence: 99%
“…These pleiotropic genes may therefore account for the covariation between melanin-based coloration, behaviour, and physiology (Roulin and Ducrest 2011), regardless of whether melanin-based coloration is involved in camouflage or whether melanin pigments participate in thermoregulation or in the protection of the integument against parasites and abrasion. Therefore, not only selection exerted on coloration but also selection exerted on genetically correlated physiological or behavioral traits may account for geographic variation.…”
Section: Introductionmentioning
confidence: 99%
“…Such variation in partial melanic pigmentation is could be due to the causes stated by Roulin and Ducrest (2011). They found that maneuvering of the genes of the melanocortin system or of their products will have significant effects on a set of characters.…”
Section: Discussionmentioning
confidence: 99%